Analisis Aksiologi Terhadap Kepemimpinan Transformasional Kepala Sekolah Dalam Perspektif Filsafat Pendidikan - Lusiana; Agus Hartono; Agus Darmuki; Mohammad Kanzunnudin (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Transformational leadership has become a leadership style that emphasizes change, inspiration, and empowerment. The transformational leadership style carried out by the principal has not yet gone hand in hand with the underlying values. This study aims to analyze the transformational leadership of the principal in the perspective of axiological philosophy. Especially related to ethical and aesthetic values ​​in decision making and teacher coaching. This study uses a qualitative approach method with the principal as the subject of research. And using literature study techniques from various references on educational philosophy and leadership management. Data were collected through participatory observation and school administrative documentation. The results of the analysis show that the axiology of transformational leadership emphasizes the importance of human values, justice, empathy, and beauty in forming a transformative and humanistic school climate. By integrating the philosophy of axiology, the principal's leadership is not only oriented towards achieving targets, but also forming the character and culture of the school that is meaningful morally and aesthetically. This finding confirms that the integration between the philosophy of values ​​and transformative leadership is not only theoretically ideal, but also real in practice in the field of education.